Energy band modulation in CuxP(x=3, 1/2)/PbTiO3 via heterogeneous erection induced benign junction interface for enhanced photocatalytic H2 evolution. (19th January 2022) - Paramanik, Lekha; Sultana, Sabiha; Parida, Kulamani
Abstract: Prompt recombination of photo-generated charges in semiconducting material strictly restrict photocatalytic process efficiency. Herein, coupling of Cux P nanoparticles and PbTiO3 nanoplates through inert atmosphere calcination process for outstanding H2 production has been reported. Uniform edging distribution of Cux P nanoparticles over PbTiO3 nanoplates; witnessed from TEM analysis revealed an intimate material contact for charge transportation to the active reaction sites of catalyst surface. Besides, junction interface between Cux P and PbTiO3 component; confirmed from XPS and Mott-Schottky analysis yield an amplified photo/electro-chemical and catalytic performance. A stronger photocurrent density via., H2 O2 electron scavenger and larger photovoltage in junction material compared with PbTiO3 counterpart; follows higher surface charge transfer efficiency and slower potential decay with longer charge carriers lifetime simultaneously. The PbTiO3 nanoplates with an optimum amount of Cux P have achieved maximum H2 production attaining conversion efficiency of 9.72%. Consequently, a type-II energy band alignment mechanism has been proposed for enhanced H2 production. Graphical abstract: Outstanding hydrogen production over Cux P/PbTiO3 p-n junction with energy conversion efficiency of 9.72%. Image 1 Highlights: Coupling of single domain PbTiO3 with low-cost Cux P via, built-in electric field. Cux P/PbTiO3 junction interface resulted in outstanding H2 production. Hybrid shows high surface charge transfer efficiency and slow potential decay.